MISALIGNMENT EFFECT ON TEST RESULTS OF THE SPLIT-HOPKINSON SHEAR BAR HAT-SHAPED METHOD - Ghani Harahap, Abdul
The Split-Hopkinson Shear Bar hat-shaped method is one of the developed techniques of the Split-Hopkinson Pressure Bar for determining the characteristic of material when subjected to shear load with a high strain rate. Misalignment is known to influence the accuracy of the final result of the Split-Hopkinson Pressure Bar. Therefore, this research is conducted to determine the misalignment effect in the Split-Hopkison Shear Bar hat-shaped method. In this research, finite element simulation will be conducted with Abaqus software. While Autodesk Inventor will be used for modeling component geometry. A convergence test will be conducted to determine the effect of element size on the accuracy and computational cost. Finite element modeling will be validated by comparing the stress-strain curve from the simulation to the theoretical and experiment. Six cases of misalignment were simulated to determine each case’s characteristic. The shear stress-strain curve shows that fluctuation tends to be higher when the output bar is misaligned than the input bar. The higher the misalignment in the output bar, the higher the fluctuation that results in a stress-strain curve. Hence, to get the more accurate testing result, support should have an offset tolerance of 1 mm, uneven height should be 0,55 mm per 1000 mm, the angle of impact face and specimen should be 0,03°, bar straightness should be 0,25 mm per 1000 mm, cone and dome impact faces should have an angle of 0,125° and 0,25°, respectively.